Fabrication of microcapsules with core‐shell structure for oral delivery of dual drugs and real‐time computed tomography imaging - Rong Cai; Long Xiao; Miaomiao Zhang; Lulu Zhao; Jingjing Zhang; Fengyi Du; Zhirong Wang (IET Nanobiotechnology)
Abstract Although multidrug combinations are an effective therapeutic strategy for serious disease in clinical practice, their therapeutic effect may be reduced because they conflict with each other medicinally in certain cases. Hence, there is an urgent need to develop a single drug carrier for precise multidrug delivery to avoid this interference. A reverse coordination method is reported that fabricates a double‐layer barium sulphate microcapsule (DL@BS MS) for two drugs separately loading simultaneously. In addition, BS nanoclusters were synthesised in situ inside the DL@BS MSs for real‐time computed tomography (CT) imaging. The results showed that the DL@BS MSs with a particle size of approximately 2 mm exhibited a uniform sphere. Because BS nanoclusters have a high X‐ray attenuation coefficient, the retention of DL@BS MSs in the digestive tract could be monitored through CT imaging in real time. More important, the core‐shell structure of DL@BS MSs encapsulating two different drugs could be released in spatiotemporal order in an acidic stomach environment. The as‐synthesis DL@BS MSs with a core‐shell structure and real‐time imaging performance provide an ideal carrier for the oral administration of multiple drugs simultaneously loaded but sequentially released.